Risk of Herpes Zoster in Patients with Rheumatoid Arthritis Undergoing Biologic Disease-Modifying Therapy - Kwon, Hyun Mi; Lee, Sang Jin; Yang, Ji Ae; Choi, Yunhee; Park, Jin Kyun; Lee, Eun Young; Song, Yeong Wook; Lee, Eun Bong (Journal of rheumatic diseases, 2017)
Objective. Rheumatoid arthritis (RA) patients suffer from an increased risk of herpes zoster (HZ) partially due to immunosuppressant medications. This study investigated HZ in RA patients treated with biologic disease-modifying antirheumatic drugs (bDMARDs), as compared with conventional DMARDs (cDMARDs). Methods. This retrospective case series study assembled record information of 277 RA patients who received bDMARDs after failure of at least one cDMARDs at Seoul National University Hospital between August 2003 and February 2015. Following capture of baseline information and identification of HZ episodes, crude HZ incidence rates per 100 patient-years (95% confidence intervals) were calculated. Results. For 718 treatment courses, 277 (38.6%) comprised cDMARDs, 66 (9.2%) infliximab, 175 (24.4%) etanercept, 95 (13.2%) adalimumab, 9 (1.3%) golimumab, 41 (5.7%) rituximab, 31 (4.3%) abatacept, and 24 (3.3%) tocilizumab. There were 37 HZ episodes, 16 during cDMARD treatment courses, and 21 accompanying bDMARDs, two with infliximab, eight with etanercept, five with adalimumab, and three each with rituximab and abatacept. The crude HZ incidence rate per 100 patient-years was 2.4 (1.4∼3.9) for cDMARDs, 2.2 (0.3∼7.9) for infliximab, 1.8 (0.8∼3.6) for etanercept, 3.7 (1.2∼8.4) for adalimumab, 3.9 (0.8∼11.0) for rituximab, and 8.5 (1.8∼23.1) for abatacept. Conclusion. We conclude that bDMARDs do not always increase the risk of HZs in RA patients, although HZ rates vary for different bDMARDs. KCI Citation Count: 1